Asuhan Keperawatan Jiwa Pada Ny. S Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Paranoid Di Ruang Arimbi RSJD Dr. Amino Gondohutomo Provinsi Jawa Tengah - Renita Juni Yanti Putri Pratama; Titi Sri Suyanti; Slamet Wijaya (STIKES Columbia Asia Medan, 2025)
Schizophrenia is a chronic mental disorder characterized by cognitive, emotional, and behavioral disturbances that may lead to aggressive behavior. Violent behavior risk is one of the most common nursing diagnoses in paranoid schizophrenia patients, which can endanger themselves, others, and the environment. This study aimed to describe psychiatric nursing care for a patient with the main problem of violent behavior risk due to paranoid schizophrenia at Arimbi Ward, RSJD dr. Amino Gondohutomo, Central Java Province. A descriptive case study design was applied, involving data collection through interviews, observation, documentation review, and literature study. The nursing process included assessment, nursing diagnosis, planning, implementation, and evaluation. The results showed that the patient exhibited symptoms of verbal aggression, tension, and refusal to take medication. Nursing interventions provided included pharmacological therapy, family psychoeducation, and group activity therapy. After the interventions, the patient showed decreased frequency of anger, improved cooperation with nurses, and willingness to participate in group activities. These findings highlight the importance of comprehensive psychiatric nursing care that integrates medical treatment and psychosocial interventions to reduce violent behavior risk in schizophrenic patients and to promote recovery and reintegration into the community.